The study of living hadith: acculturation of local culture religion in mendoa Asyura Tradition in West Sumatra - Kirin, Arwansyah; Saputra, Edriagus; Eka Eramahi, Eka Eramahi; Nana Gustianda, Nana Gustianda (2024)
Mandoa Ashura is a community tradition that is carried out as the community's implementation of the meaning of the prophet's hadith in honoring the day of Ashura by fasting. However, however, the practice carried out by the community is different from the meaning of the hadith, thus However, the practice carried out by the community is different from the meaning of the hadith, so that it appears that the meaning of the hadith is distorted by the community into a procession of mandoa tradition. This article aims to describe the implementation of the Ashura mandoa tradition in the community of jorong lubuk alung, Agam Regency. This research is a living hadith study that is a living hadith study that uses qualitative methods with a phenomenological approach. The findings The findings describe that the mandoa ashura is a teaching from Shaykh Burhanuddin as a scholar spreading Islam in West Sumatra and as a tribute to the month that has a lot of history. West Sumatra and as a tribute to the month that has a lot of history, worship and social values. and the value of worship and social community. The findings also show the understanding of local scholars use the proposition of the Prophet's hadith related to the command to fast in the month of Ashura, which coincides with the month of the month of Ashura which coincides with the month of Muharram and the hadith is considered maqbul by the scholars. the scholars. Another finding shows the use of the Ashura mandoa carried out by the community, namely as a form of taqarrār. the community, namely as a form of taqarrub to Allah SWT, taking ibrah the events in the month of Ashura, and a form of self-introspection in running life